1997
DOI: 10.1139/b97-829
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in sexual and agamospermous Amelanchier (Rosaceae)

Abstract: Agamospermy, which is almost always associated with polyploidy, is often assumed to reduce variation and foster evolution of microspecies. We tested for the occurrence of microspecies by comparing variation of sexual Amelanchier bartramiana and facultatively agamospermous (asexually seed-producing) Amelanchier laevis. We assessed within- and among-population variation of 222 individuals from six Maine populations of each species for eight morphological variables. Mahalanobis distances between individuals and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Sorbus -related entities are notorious in taxonomy due to complexity in phenotypes resulting from interspecific hybridization and facultative agamospermy [ 39 , 69 , 70 ]. Apomictic microspecies confound systematic resolution of agamic complexes using nuclear markers [ 71 ]. Phylogenies based on nuclear genes may suffer from paralogue problems and chloroplast markers would work better at the very beginning when no clear ideas are available for classification.…”
Section: Discussionmentioning
confidence: 99%
“…Sorbus -related entities are notorious in taxonomy due to complexity in phenotypes resulting from interspecific hybridization and facultative agamospermy [ 39 , 69 , 70 ]. Apomictic microspecies confound systematic resolution of agamic complexes using nuclear markers [ 71 ]. Phylogenies based on nuclear genes may suffer from paralogue problems and chloroplast markers would work better at the very beginning when no clear ideas are available for classification.…”
Section: Discussionmentioning
confidence: 99%
“…Sang & al., 1995;Wendel & al., 1995;Aguilar & al., 1999) due to reduced/lacking recombination rate and meiotic paring in the case of non-homologous ITS regions (cf. Campbell & al., 1997;Fehrer & al., 2009;Hörandl & al., 2009;Záveská-Drábková & al., 2009). However, most of the intra-individual polymorphic sites found in the P. alpicola group (excluding P. alpicola s.str.)…”
Section: Discussionmentioning
confidence: 99%
“…Morphological data collected from the M. section Chloromeles accessions demonstrated continuous variation between the three taxa to which accessions were initially assigned, leading DICKSON et al (1991) to conclude that the name M. coronaria should be applied to all of this material. Similarly polyploid, apomictic Amelanchier laevis WIEGAND was shown not to be subdivided into microspecies by means of statistical analyses of generalized distances calculated from eight morphological descriptors (CAMPBELL et al 1997). These analyses indicated that variation within and between local populations of A. laevis was smaller than in diploid, sexual A. bartramiana (TAUSCH) ROEM., and did not provide evidence for population differentiation in A. laevis.…”
mentioning
confidence: 99%